2012
DOI: 10.1007/s00441-012-1380-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the male reproduction-related gene (Mar-Mrr) in the spermatic duct of the giant freshwater prawn, Macrobrachium rosenbergii

Abstract: Phosphorylated sperm proteins are crucial for sperm maturation and capacitation as a priori to their fertilization with eggs. In the freshwater prawn, Macrobrachium rosenbergii, a male reproduction-related protein (Mar-Mrr) was known to be expressed only in the spermatic ducts as a protein with putative phosphorylation and may be involved in sperm capacitation in this species. We investigated further the temporal and spatial expression of the Mar-Mrr gene using RT-PCR and in situ hybridization and the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Meanwhile, the other two testis-specific genes, including male reproductive-related protein Mar-Mrr and male reproductive tract-specific Kazal-type proteinase inhibitor, showed a specific testicular expression pattern. Earlier studies had demonstrated that Mar-Mrr was specially expressed in the male reproductive tract, and was required for sperm function [11,14,65]. Thus, combining the current results indicates that Mar-Mrr is implicated in male-reproduction.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Meanwhile, the other two testis-specific genes, including male reproductive-related protein Mar-Mrr and male reproductive tract-specific Kazal-type proteinase inhibitor, showed a specific testicular expression pattern. Earlier studies had demonstrated that Mar-Mrr was specially expressed in the male reproductive tract, and was required for sperm function [11,14,65]. Thus, combining the current results indicates that Mar-Mrr is implicated in male-reproduction.…”
Section: Discussionsupporting
confidence: 81%
“…Although the Z and W chromosomes have not been identified, the results still provided a useful resource and comprehensive knowledge of genomic structure of M. rosenbergii [10]. However, sex-related genes and a list of biological pathways involved in gonads development have been revealed [11][12][13][14][15][16], the potential molecular mechanisms of sex determination in M. rosenbergii are still not well understood.Currently, along with the emergence of next generation sequencing (NGS), RNA-sequencing (RNA-seq) was widely applied to detect the expression profiles of genes and identify the sex-related genes in aquaculture species, especially those lacking genomic sequences, due to its high throughput and low cost. To date, some progresses have been made in the characterization of sex-related genes and pathways in M. rosenbergii [16], Macrobrachium nipponense [17], Silver Sillago [18], Olive Flounder [19], Pacific abalone [20], Pacific white shrimp [21], catfish [22], and Acipenser dabryanus [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serine threonine protein kinases were found to be highly expressed in the testes of E. sinensis [ 50 ]; the authors suggesting that STPKs may play a key role in both mitotic and meiotic divisions and extensive cellular re-modelling through cell cycle phases during spermatogenesis. In M. rosenbergii , a male reproductive-related protein homologous with STPK was found to be expressed exclusively in the sperm ducts as a protein with a putative role in phosphorylation and with a function involved with sperm capacitation and/or fertilization [ 51 ]. In N. norvegicus , 24 transcripts annotated as STPK were detected exclusively in the testes suggesting that several isoforms could have different functions in male reproduction (Additional file 4 : Table S3).…”
Section: Discussionmentioning
confidence: 99%
“…An initial step towards understanding the molecular basis of the genetic regulation of maturation has already been initiated for M . rosenbergii [ 18 , 19 , 20 ], and this has included a focus on the progress of sexual differentiation ( i.e. , sex-linked markers) [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%